Structural Models in Technical Texts as a Result of a Linguistic-Pragmatic Analysis - Pankuchova, Katarína; Gavlakova, Andrea (Communications - Scientific letters of the University of Zilina, 2010)
Typical structural models in technical language, their use in understanding, translating and producing technical texts as well as in technical language teaching, engineering and technology (word-formation, grammatical and syntactical structural models and their pragmatic-linguistic analysis). Comparison of typical linguistic structures in Slovak, German and English technical texts.